Cardiorespiratory optimal point as a submaximal evaluation tool in endurance athletes: An exploratory study - Oyarzo-Aravena, Alexis; Arce-Alvarez, Alexis; Salazar-Ardiles, Camila; Ramirez-Campillo, Rodrigo; Alvarez, Cristian; Toledo, Camilo; Izquierdo, Mikel; Andrade, David C. (Frontiers in Physiology, 2023)
The cardiorespiratory optimal point (COP) represents the lowest minute ventilation to oxygen consumption ratio (VE/VO2) and can be estimated during a CPET at submaximal intensity when an exercise test until volitional fatigue is not always advisable (i.e., a conflict zone where you cannot be confident of the security because near-competition, off-season, among other). COP’s physiological components have not been wholly described yet. Therefore, this study seeks to identify the determinants of COP in highly trained athletes and its influence on maximum and sub-maximum variables during CPET through principal component analysis (PCA) (explains the dataset’s variance). Female (n=9; age, 17.4±3.1 y; maximal VO2 [VO2max]), 46.2±5.9 ml/kg/min) and male (n=24; age, 19.7±4.0 y; VO2max, 56.1±7.6 ml/kg/min) athletes performed a CPET to determine the COP, ventilatory threshold 1 (VT1) and 2 (VT2), and VO2max. The PCA was used to determine the relationship between variables and COP, explaining their variance. Our data revealed that females and males displayed different COP values. Indeed, males showed a significant diminished COP compared to the female group (22.6±2.9 vs. 27.2±3.4 VE/VO2, respectively); nevertheless, COP was allocated before VT1 in both groups. PC analysis revealed that the COP variance was mainly explained (75.6%) by PC1 (expired CO2 at VO2max) and PC2 (VE at VT2), possibly influencing cardiorespiratory efficiency at VO2max and VT2. Our data suggest that COP could be used as a submaximal index to monitor and assess cardiorespiratory system efficiency in endurance athletes. The COP could be particularly useful during the offseason and competitive periods and the return to the sports continuum.